Simulation of autothermal hydrogen-producing limestone calcination for calcium looping in turbulent fluidized bed reactors. (2nd February 2020) - Ebneyamini, A.; Grace, J.; Lim, C.J.; Ellis, N.; Elnashaie, S.S.E.H.; Mahecha-Botero, A.
Highlights: Process provides autothermal hydrogen-producing sorbent regeneration for Ca-looping. A unique correlation is proposed for gaseous feed composition in this technology. The combined process is modeled in turbulent fluidized bed membrane reactors. System performance is analyzed for a wide range of operating conditions. Pressure, temperature, feed composition and solids residence time are key factors. Abstract: This paper investigates the performance of combining limestone calcination with catalytic methane reforming and combustion in turbulent fluidized bed membrane reactors. The equilibrium performance of the process was evaluated using Aspen simulation, with a unique correlation to estimate the required gaseous feed composition for autothermal and complete sorbent regeneration at operating temperatures of 800–900 °C. A one-dimensional, isothermal, steady-state kinetic model is then employed to study the performance of the four-in-one (combustion + reforming + calcination + optional membrane separation) integrated process under turbulent fluidization conditions. The simulation results demonstrate the high potential of this novel sorbent regeneration technique for autothermal, rapid and hydrogen-producing limestone calcination. The performance is shown to depend strongly on the sorbent/total gas molar feed ratio, operating temperature, operating pressure and sorbent residence time.